PENGEMBANGAN VIDEO ANIMASI BERBASIS KARAKTER CINTA TANAH AIR UNTUK ANAK USIA DINI - Miranda, Dian (Jurnal Visi Ilmu Pendidikan, 2019)
AbstrakThe aim of this study is to develop animated characters based on love of homeland for early childhood. The research method used in this study is R & D research. The development model in this study refers to the 4D research and development model (four-D). According to Thiagarajan (1974) the 4D research and development model consists of 4 main stages, namely define, design, develop, and disseminate. The data analysis technique used in this study is a mixed analysis technique that is a combination of qualitative analysis and quantitative analysis. The results of video validation carried out by 4 validators were an average of 2.8 with a maximum score of 3, included in the very feasible category used as learning media to develop the character of love for the homeland in early childhood.Kata Kunci: animated video, the character of love for the homelandÂ